2013
DOI: 10.1155/2013/984678
|View full text |Cite
|
Sign up to set email alerts
|

The Improvement of Emotion and Attention Regulation after a 6-Week Training of Focused Meditation: A Randomized Controlled Trial

Abstract: Self-regulatory trainings can be an effective complementary treatment for mental health disorders. We investigated the effects of a six-week-focused meditation training on emotion and attention regulation in undergraduates randomly allocated to a meditation, a relaxation, or a wait-list control group. Assessment comprised a discrimination task that investigates the relationship between attentional load and emotional processing and self-report measures. For emotion regulation, results showed greater reduction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 61 publications
4
39
0
3
Order By: Relevance
“…These findings support other studies which also evaluated emotional and attentional variables following short interventions varying between three and seven days (Chen et al, 2013;Ding et al, 2014;Tang et al, 2007;Zeidan, Johnson, Diamond, et al, 2010;Zeidan, Johnson, Gordon, et al, 2010). The results also corroborate a study which evaluated a six-week version of the same training of focused meditation, particularly in relation to the fact that in both interventions there was a reduction in the negative affect, although no significant change was observed in the positive affect, as well as reduction of trait anxiety (Menezes et al, 2013). In addition to this, the results found complement the literature regarding short training programs, demonstrating that positive effects can also occur through an intervention using focused meditation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings support other studies which also evaluated emotional and attentional variables following short interventions varying between three and seven days (Chen et al, 2013;Ding et al, 2014;Tang et al, 2007;Zeidan, Johnson, Diamond, et al, 2010;Zeidan, Johnson, Gordon, et al, 2010). The results also corroborate a study which evaluated a six-week version of the same training of focused meditation, particularly in relation to the fact that in both interventions there was a reduction in the negative affect, although no significant change was observed in the positive affect, as well as reduction of trait anxiety (Menezes et al, 2013). In addition to this, the results found complement the literature regarding short training programs, demonstrating that positive effects can also occur through an intervention using focused meditation.…”
Section: Discussionsupporting
confidence: 89%
“…In the focused meditation technique, the practitioners train sustained and concentrated attention on a single focus in a more systematic way, so as to develop the skill of more easily not becoming engaged, or of disengaging oneself from the usual mental processes, which are often automatized and dysfunctional (Lutz, Slagter, Dunne, & Davidson, 2008). This meditation has already been tested in one study, evaluating a six-week intervention, whose results showed a reduction in the self-reporting of negative affect and of trait anxiety, and an improvement in the performance of attention in healthy university students (Menezes et al, 2013).…”
mentioning
confidence: 99%
“…O treino de meditação baseouse no estudo de Menezes et al (2013). O mesmo incluiu seis encontros semanais consecutivos com uma duração aproximada de uma hora e quinze minutos.…”
Section: Procedimentosunclassified
“…Programas baseados na meditação constituem uma modalidade de intervenção que vem sendo crescentemente aplicada no ambiente universitário com o objetivo de reduzir o estresse, bem como aumentar o bem-estar e a qualidade de vida (Fan, Tang, & Posner, 2014;Greeson, Juberg, Maytan, James, & Rogers, 2014;Jain et al, 2007;Menezes et al, 2013;Oman, Shapiro, Thoresen, Plante, & Flinders, 2008;Regehr, Glancy, & Pitts, 2013). No Brasil, um estudo realizado na Universidade Federal do Rio Grande do Sul demonstrou que existe um grande interesse por parte dos universitários em participarem deste tipo de intervenção (Menezes, Fiorentin, & Araujo, 2012).…”
unclassified
See 1 more Smart Citation